PEREMPUAN DAN PEMBERDAYAAN EKONOMI KELUARGA MELALUI PEMBUATAN PONGASI DI DESA WENGGUDUKU KABUPATEN KONAWE - Syamsumarlin, Syamsumarlin (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2012)
As it has been known, traditional alcoholic drink namely pongasi aremade by Wengguduku peoplein Konawe district. Pongasi production hasbeen a tradition of the people of that village as well as to earn money whichis difficult to leave particularly by housewives of the village because thissort of drink is delivered in ceremonies among the societies. Besides, theproduction support their economic condition financially. Although the stateforbids the production of pongasi, the housewives in the village still producethe drink due to tradition consideration. Based on that reality,social impact which is caused by pongasi distribution will be observed by etnoghraphy method by collecting data by collecting data, observation and interviewtowards research object based on field data. The result of this research willbe considered as reference for antropologhy of law for the society.